Penyuluhan tentang Pentingnya Etika dan Moral dalam Pendidikan - Pomarida Simbolon; Nagoklan Simbolon; Ried Rivaldo Simbolon; Selfin Yanti Telaumbanua; Teofilus Rivaldo Zagoto (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
Moral ethics can be defined as a set of principles or rules that govern individual behavior in educational relationships. In the context of education, moral ethics plays a crucial role in shaping how students interact with one another, how they respect teachers, and how they understand and apply the values taught. Educational ethics encompasses more than just academic aspects; it also teaches the values that permeate social life. Good moral ethics can help individuals become honest, responsible, and compassionate toward others. Ethical and moral education plays a crucial role in shaping students' character and personality. Ethics, as a collection of values and principles that govern human behavior, and morality as a view of right and wrong, serve as the foundation for shaping students' attitudes, responsibility, and integrity in their daily lives. Through education that instills values such as honesty, justice, empathy, and social responsibility, students are not only equipped with intellectual knowledge but also shaped into individuals with morals and ethics. Thus, education produces not only academically intelligent individuals but also individuals with noble character. Through educational ethics, we can realize a more harmonious, just, and respectful education.